NILAI-NILAI PENDIDIKAN AKHLAK DALAM KITAB AL-ARBA’IN AL-NAWAWIYAH KARYA IMAM NAWAWI SEBAGAI UPAYA PEMBENTUKAN KARAKTER - Alifa Amalia Izzati; Nurul Azizah; Abbad Hanif Al Falah; Abid Sholihin (Prodi Pendidikan Agama Islam STAIN Mandailing Natal, 2022)
Character education is an important education instilled by fellow human beings for the formation of human beings with a charitable character. This study aims to uncover the content of Imam Nawawi's kitab Al-Arba'in al-Nawawiyyah about the values of character education towards fellow human beings. This type of research is library research where data is searched through articles and books, then sorted, and collected and presented by the author. The findings show that the values of character education contained in this book are obedient attitude, advising, saying good, restraining anger or ego, keeping oral, glorifying neighbors and guests, philanthropy, maintaining honor and ukhuwah (brotherhood), helping each other, forgiving each other. Then the cultivation of his morals can be done by means of exhortation, exemplary, habituation, Targhib and Tarhib. In its cultivation, there are factors that influence it, including internal (psychological) and external (family, environment, social media).